TEKNOLOGI BIOPORI DALAM PENGELOLAAN SAMPAI ORGANIK DI DESA CAU BELAYU, TABANAN BALI - Rima Dewanti Putri; Putri Ekaresty Haes; I Gede Eka Sanjaya; Ida Ayu Gede Sukmarini W; I Dewa Gede Angga W (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2022)
This community service activity (PKM) is a collaborative activity between lecturers and students that must be carried out as part of the implementation of the Tridharma of higher education. Garbage is a problem that still cannot be solved in various regions in Indonesia, especially in the village of Cau Belayu, Tabanan Regency. Effective waste management can provide a solution in overcoming floods in the rainy season, one of which is the vetiver system and biopori technology. These two systems can accelerate the absorption of water into the soil. This method of implementing community service is carried out by providing education to the community about vetiver systems and biopori technology, and after that, implementing the two programs directly on the community pages that have been deemed worthy of the two programs. Both systems provide many benefits to the community, namely reducing organic waste and fertilizing the soil, this is due to a biological process that will turn the waste into compost. The holes are made, then given organic waste which will trigger soil biotas such as worms and ants, and plant roots to create cavities in the soil. This community service activity is carried out through three stages, namely assessment of the village, implementation, and evaluation. As a result of this community service, now the people of Cau Belayu village have implemented these two technologies in people's homes even though they use simple equipment. In addition, the two systems are also implemented in the environment around the temple and the shrines in the village.